The Use of Digital Media as a Strategy for Lowering Anxiety in Learning English as a Foreign Language - Septiarini Makodamayanti; Deli Nirmala; Catur Kepirianto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2020)
In the modern era, the use of English now being spreading and penetrated to many fields, including educational field. Thus, learning a foreign language, particularly English is needed by students or learners. However, there are personality factors such as anxiety, that may give either good or bad influences. Therefore, strategy in learning is needed to help the learners encountering their learning process. Various strategies can be used in learning a foreign language. This study discusses about the role of digital media in helping lowering learners’ anxiety in learning foreign language especially English. Several studies are found and have conducted their analysis concerning the use of digital media such as social media, video games, video and audio, in foreign language learning. The results of the review show that digital media which offers low pressure to its users is advantageous and can be effectively used to help the learners in comprehending English so that they feel less anxiety and be more confident in learning and using English as a foreign language.